Proteome analysis of wheat seed embryo (Tritium aestivum) in tolerant and susceptiblecultivars under drought stress in second germination phase - علی شایانفر; رضا توکل افشاری; هوشنگ علیزاده; عبدالرحمن رسول نیا (علوم و فناوری بذر ایران)
Drought stresses are unfavorableenvironmentalfactors that affect crop growth especially in the early stagesof germination. Seed germination is a complex process that involves three main phases that in phases before radicle protrusion (second germination phase) many process was occurred in embryo axes as living part of seed. This study was carried out to understand the effectof drought stress onprotein patterns in the second phase of germination. In order to analysis the effects of drought stress (-12 bar) on wheatembryo proteome (Sardari and Qods respectively tolerant and susceptiblecultivar), factorialexperiment was conducted in a Randomized completely block designwith three replications. Drought stress decreased germination percentage and causedadverse effects on the proteins pattern. Two-dimensional gel electrophoresis analysis of wheat embryo axis showed 1000spotswerereproducible that 25 spots between treatments indicated significant differences on 5% level. In control condition, in comparison tolerant to susceptiblecultivar, 10 and 13 spots and in stress condition, 11 and 13 spots were down and up regulated respectively.Possible proteins such as alpha amylase inhibitor, 1–Cys peroxiredoxin and Heat shock proteins may be involve in drought stress during seed germination. The results showed that the frequency of these proteins under drought stress depends on severity and amount of stress and imbibition time.